The Effect of Use of Contextual Teaching and Learning (CTL) Learning Model on Understanding the Concept of Waves of Coastal School Students - Ilyas Ilyas; An Nisaa Al Mu’min Liu; Hamsah Doa (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the understanding of the concept of wave material using the Contextual Teaching and Learning (CTL) learning model of coastal area school students. This type of research is quantitative research. It uses descriptive statistical analysis and inferential statistics to illustrate data understanding of the wave material concept of students in the Coastal Regional Schools (Private Senior High School of Mutmainah Ende) using the Contextual Teaching and Learning (CTL) learning model. Data collection techniques used in this study were test techniques. From the results of descriptive analysis, it shows that the average understanding of the concept is 80.75 in the good category. The results of inferential statistics show the t count is 5.885, sig (2-tailed) 0,000. Because the sig (2-tailed) value of 0,000 is smaller than 0.05, thus it can be concluded that the use of the Contextual Teaching and Learning learning model influences the understanding of the wave concept in coastal school students.Keywords: concept understanding, waves, contextual teaching and learning Penelitian ini bertujuan untuk mengetahui pemahaman konsep materi gelombang menggunakan model pembelajaran Contextual Teaching and Learning(CTL) siswa sekolah daerah pesisir pantai. Jenis penelitian ini adalah penelitian kuantitatif, dengan analisis statistik deskriptif dan statistik inferensial untuk menggambarkan data pemahaman konsep materi gelombang siswa Sekolah Daerah Pesisir Pantai (SMP Swasta Mutmainah Ende) menggunakan model pembelajaran Contextual Teaching and Learning(CTL). Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik tes. Dari hasil analisis deskriptif menunjukkan bahwa rata-rata pemahaman konsep gelombang siswa adalah 80,75 berada dalam kategori baik. Sedangkan hasil statistik inferensial menunjukkan nilai t hitung 5,885, sig(2-tailed) 0,000. Karena nilai sig(2-tailed) 0,000 lebih kecil dari 0,05 hal ini menunjukkan bahwa penggunaan model pembelajaran Contextual Teaching and Learning berpengaruh terhadap pemahaman konsep gelombang siswa sekolah daerah pesisir pantai.Kata kunci: pemahaman konsep, gelombang, contextual teaching and learning